PERAN MEDIA SOSIAL DAN PENENTUAN HARGA DALAM MEMPERTAHANKAN PELANGGAN - Khairunnisa, Nabilah (Fakultas Ekonomi Dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2024)
The development of the halal industry in the skincare sector increases very rapidly every year. Islam allows facial skin care as a form of gratitude for maintaining the gifts that God has given to his people. The face is the first impression when we meet, having facial skin problems causes a feeling of insecurity for some individuals. Generation Z is one of the factors in the rapid development of skincare in Indonesia, of course by looking at the halalness of products that have been verified by BPOM and Halal MUI. This research aims to determine the influence of social media marketing, religiosity, price and halal brand personality on loyalty to The Originote skincare brand in generation Z in Jabodetabek. The sampling method in this research used non-probability sampling with a purposive sampling technique, namely the Likert scale. The research uses a quantitative approach by collecting data using the IBM SPSS Statistics 26 application. The results of the research show that social media marketing and price have a positive and significant effect on loyalty to The Originote skincare brand in generation Z in Jabodetabek. Meanwhile, religiosity and halal brand personality have a positive and insignificant effect on loyalty to The Originote skincare brand in generation Z in Jabodetabek.